The Effect of Pethidine Analgesia on Labor Duration and Maternal-Fetal Outcomes: Pethidine and Labor Duration - Kadirogullari, Pinar; Yalcin Bahat, Pinar; Sahin, Busra; Gonen, Ilker; Seckin, Kerem Doga (Acta Biomedica Atenei Parmensis, 2021)
Background: Opioid analgesics had been used from time to time for treating labor pain. However, their use have been concerning. The aim of this study is to evaluate the effect of pethidine on duration of active phase of labor, labor pain and maternal-neonatal outcomes.Methods: In the present case-control study, the study group received a 50 mg pethidine intramuscular injection upon the start of active phase of labor, and the control group consisted of patients who receive placebo injeciton. In both groups, vital signs were measured before, and at 0, 5, 15, 30, 45 and 60 minutes after the injection. Pain intensity was evaluated with Visual Analogue Scale (VAS) prior to, and 1 hour and 2 hours after injection. Data regarding labor phase durations, maternal side effects, newborn APGAR scores and fetal respiratory problems were recorded.Results: 102 patients in Pethidine group and 92 patients in control group, were included into the study. Labor pain VAS-scores were significantly lower in the study group (p